COMPREHENSIVE REVIEW ON MENTAL HEALTH FIRST AID IN EMERGENCY SERVICES - 1Hadi Mohammed Almohammed, 2Ahmed Hussain Saleh Alfaqir, 3MAHDI SALEH MAHDI ALSHERYAH, 4Ali Mohammed Nasser Al Mohammed, 5Hassan Ali Maed Alhamamah, 6Mohammad Mesfer Al Alabaalteheen, 7Abdulaziz Mohammed Nasser Al-Mohamad, 8Mohammed Hady Ali Alyami (Chelonian Research Foundation, 2022)
Mental health issues among crisis specialists are recognized as serious issues. Mental well-being administrations Mental Health First Aid (MHFA) which may be a nursery of trust and compromise. This comprehensive research illustrates the potential of MHFA within the emergency office. Recent discoveries indicate that the MHFA program increases mindfulness, decreases disgrace, and energizes early supplication. Be that as it may, issues such as resource assignment and organizational amassing remain. It is suggested that MHFA be included in the preparation and proceed to be educated around the advance of the study. Keywords: Mental Health First Aid, Emergency Services, Mental Health Awareness, Stigma Reduction, Early Intervention